When the moon hits your eye - Scalzi, John, 1969- (Tor, 2025)
The moon has turned into cheese. Now humanity has to deal with it. For some it's an opportunity. For others it's a moment to question their faith: In God, in science, in everything. Still others try to keep the world running in the face of absurdity and uncertainty. And then there are the billions looking to the sky and wondering how a thing that was always just there is now... something absolutely impossible. Astronauts and billionaires, comedians and bank executives, professors and presidents, teenagers and terminal patients at the end of their lives -- over the length of an entire lunar cycle, each get their moment in the moonlight. To panic, to plan, to wonder and to pray, to laugh and to grieve. All in a kaleidoscopic novel that goes all the places you'd expect, and then to so many places you wouldn't. It's a wild moonage daydream. Ride this rocket. --